STUDY ON THE IMPACT OF THE MARKET SITUATION ON THE ECONOMIC RESULTS OF A COMPANY SPECIALIZED IN THE SALE OF JEWELRY - Mariana JUGĂNARU; Felicia RUSU; Daniela POPESCU (Management & Marketing)
The economic performance of any society/company depends on the decisions made in organizing its entire activity (in all aspects, including marketing), as well as its ability to ensure an outward orientation. From a marketing perspective, understanding the multitude of connections, relationships that each company develops, and being aware of the importance of their impact on its activity, have led to an increased interest in studying the external environment. Anticipating the future evolution of external environment components and potential implications for the company's activity are important concerns for marketing activity management. This article presents a study based on the analysis and interpretation of the economic results achieved by a Romanian company during the Covid-19 pandemic. The aspects identified and conclusions drawn from this study highlight the fact that the change in market conditions has been an important element/factor for the company's performance and image.